Orientation for innovating pedagogical training curriculum for technical/vocational teachers - Đỗ Mạnh Cường (Journal of Technical Education Science, 2014)
These current renovation programs haven’t been efficiency as desire. Based on experiences IN organization and implementation pedagogical training projects for technical/vocational teachers and comparison to other existed courses, we have analyzed reasons lead to these programs limits and proposed solutions. The results show that changing in philosophy and approaches design curriculum is necessary to change curriculum and approve the efficient training. All the results archiving at our institute have proved that our solutions can solve and bring better outcomes at changing and enhancing pedagogical competences for technical/ vocational teachers.